(untitled) (Delta Medical College Journal, 2014)
Importance of imaging in all clinical or medical research, and especially, of Computerized Axial Tomography (CAT scan), has demonstrated a unique place in diagnostic or radiation therapy. Two-dimensional images of internal structures of the body are examined and reported. This process of imaging, any anatomical location, viz. head and neck, thorax, pelvis, etc. takes about 30 seconds to perform with a minimal dose of less than 1.6- 2.0 mGy. The images are constructed by the hardware with software algorithm, using the attenuation and absorption of X rays of tissues, of varying electron densities of the anatomical structures. Sometimes a contrast dye is injected to a patient intravenously, rectally or orally, to make hollow or fluid-filled structures such as blood vessels more visible. Radiologists and radiation oncologists are confronted with a task to delineate the information of the CT images to a meaningful diagnosis. The images are, therefore, valuable for diagnostic reports, some of these may relate to cancerous tumors and tissues. Cancer treatment, radiation therapy or else, from such observations may start. But an artifact and distortion on such images will contribute to erroneous and/or unusable interpretations in offering a clinical report to provide wrong clinical decisions. The implications of the presence of distortion in CT images is, for a patient, described here so as to instruct the experts, in medical and clinical fields, to rectify the situation in acquiring a sharp and flawless image or in reaching the correct clinical goal. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17789 Delta Med Col J. Jan 2014; 2(1): 3-8